Dsg2 ectodomain organization increases throughout desmosome assembly - William F. Dean; Rose M. Albert; Tomasz J. Nawara; Melanie Ubil; Reena R. Beggs; Alexa L. Mattheyses (Cell Adhesion & Migration, 2024)
Desmosomes are intercellular junctions that regulate mechanical integrity in epithelia and cardiac muscle. Dynamic desmosome remodeling is essential for wound healing and development, yet the mechanisms governing junction assembly remain elusive. While we and others have shown that cadherin ectodomains are highly organized, how this ordered architecture emerges during assembly is unknown. Using fluorescence polarization microscopy, we show that desmoglein 2 (Dsg2) ectodomain order gradually increases during 8 h of assembly, coinciding with increasing adhesive strength. In a scratch wound assay, we observed a similar increase in order in desmosomes assembling at the leading edge of migratory cells. Together, our findings indicate that cadherin organization is a hallmark of desmosome maturity and may play a role in conferring adhesive strength.